Uterine rudimentary horn and ovarian endometriosis with a special emphasis on VACTERL association: a report of two cases - Bhadwal, Arushi; Sharma, Sonam; Ranga, Sunil (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Mullerian duct anomalies are a wide and complex spectrum of congenital abnormalities that are often associated with renal as well as axial skeletal anomalies or can be a part of multiple malformation syndrome and may cause numerous other gynecological complications. We herein describe two young girls who presented with a common complaint of abdominal pain and had normal secondary sexual characteristics.The first case had a history of imperforate anus, and urinary incontinence due to renal anomalies including ectopic kidney, renal agenesis, duplex ureter along with sacral agenesis which were confirmed on imaging. VACTERL (V-vertebral anomalies, A-anorectal malformations, C-cardiovascular anomalies, T- tracheoesophageal fistula, E-esophageal atresia, R-renal anomalies, and L-limb defects) association was considered. To the best of our knowledge, this is the fourth such case with concomitant VACTERL association. Surgical resections were performed in both cases, after clinical-radiological correlation. Histopathological examination of specimens revealed a unicornuate uterus with a rudimentary horn and ovarian endometriosis. In conclusion, early identification and prompt intervention through a multidisciplinary approach are paramount for managing such anomalies as they can have many detrimental implications.